Automata-Based Analysis of Stage Suspended Boom Systems - Anping He; Jinzhao Wu; Shihan Yang; Yongquan Zhou; Juan Wang (Journal of Applied Mathematics)
A stage suspended boom system is an automatic steeve system orchestrated by the PLC (programmable logic controller). Security and fault-recovering are two important properties. In this paper, we analyze and verify the boom system formally. We adopt the hybrid automaton to model the boom system. The forward reachability is used to verify the properties with the reachable states. We also present a case study to illustrate the feasibility of the proposed verification.